The implementation of 5S practice to improve better working condition at a bakery company - Siti Nurain, Abd Rani (2016)
The aim of this study was to identify on the implementation of 5S practices in the company Mawar Bakery in specific areas such as warehouses, manufacturing and packaging and labelling division, whether the level of good working conditions can be improved or not. The objective of this study is divided into three, namely to evaluate (a) the current 5S practice at bakery company , (b) identify practices area that can be improved in terms of the implementation of 5S and (c) to propose a solution to improve the 5S practice in the company in the context of improve working conditions better. Descriptive analysis based on interview transcripts using coding and theme method to analyze data. The instrument is the interview conducted in some selected area such as warehouses, manufacturing and, packaging and label the parts. A total of 11 participants were interviewed using focus group method in accordance with sections that have been selected. The results show that more solution needs to be done by the company to upgrade the existing practice of 5S to improve working conditions to be better than now. This is because, the study found that most employees do not understand the concept and the implementation of 5S practices. Therefore, researchers have suggested three ways that you can solve taken by the company to handle this problem. The proposed measures that include program / training about the correct implementation of the 5S practice, 5S implementation plan concept using PDCA and the last one is regular audits.